Rethinking sociality and health through transfiguration - Bernhard Hadolt; Brigit Obrist; Dominik Mattes (Medicine Anthropology Theory, 2020)
In this introductory article to the Special Section, we intend to literally bring sociality to (bodily) life and ask what medical anthropology might gain by using the lens of sociality for a better understanding of the phenomena it is concerned with. Conversely, we probe how the field of health and illness – including themes concerning embodiment, vulnerability, suffering, and death – might help to further spell out the notion of sociality both conceptually and methodologically. Drawing on the contributors’ ethnographic enquiries into contemporary health phenomena in East Africa, South America, and Western Europe, we do so by bringing sociality into conversation with transfiguration. By this we refer to: (1) the constantly unfolding processes of particular extended figurations encountering, affecting, and becoming enmeshed in each other; as well as (2) the (temporarily) stabilized figurational arrangements emerging from these enmeshments. It is our hope that this notion of transfiguration will help render visible the modalities through which human engagements with each other and the world form diverse arrangements. Moreover, we aim to better understand the processes by which these arrangements – which we term ‘extended figurations’ – interact with each other, change over time, and possibly vanish and make way for others. A detailed appreciation of the workings of these extended figurations, we believe, can significantly enhance our comprehension of the particular processes of change that stand at the center of our ethnographic interest. In this sense, the concept of transfiguration constitutes one possible way of structuring the messiness and complexity of sociality for analytical purposes.